Knowledge of Public Environmental Health with Covid-19 Prevention Behavior at the Jalan Gedang Public Health Center Bengkulu City - Raju Sungsang Amir; Nopia Wati; Agus Ramon; Riska Yanuarti; Fauzia Farah Az Zahra (Disease Prevention and Public Health Journal, 2022)
Background: The highest spread of Covid-19 cases in 9 sub-districts in Bengkulu City was Gading Cempaka District, with 86 positive cases, 46 recovered, and 3 died. People do not comply with health and personal hygiene protocols such as washing hands and using masks, do not behave in a healthy life, and lack public awareness in maintaining environmental cleanliness. In addition, the community still litters in several places and lacks knowledge and understanding of clean water and household waste management properly. This study aimed to determine the relationship between public environmental health knowledge and Covid-19 prevention behavior in the Working Area of ​​Jalan Gedang Health Center, Bengkulu City. Method: The design used in this research is quantitative research using a cross-sectional approach. This research took place in the area of ​​Jalan Gedang Health Center, Bengkulu City. This research was conducted in January – February 2021. The population was 15,726 people; a sample of 40 people was taken from the minimum sample calculation using a simple random sampling technique. The process of collecting data using a questionnaire and analyzed by univariate and bivariate. Results: The results showed that respondents with good knowledge were 21 people (55%) and 19 people (45%). There is a significant relationship between environmental health knowledge and community behavior toward preventing Covid-19 in the Jalan Gedang Health Center Work Area, Bengkulu City. The results showed p-value (0.001) > 0.05, OR = 7.500 with 95% CI (1.798-31.283). This means that knowledgeable respondents are 7.5 times less likely to behave less well in preventing Covid-19 compared to well-informed respondents. Conclusion: Environmental health knowledge has a significant relationship with Covid-19 prevention behavior. Researchers advise the public to always maintain a clean environment and live a healthy life to avoid the transmission of the Covid-19 disease.